Income Analiysis of Langsat Farmers - Yerike Yerike; Jumriani Dambe; Hamsah Hamsah (Journal La Lifesci, 2026)
The purpose of this study was to analyze the income of farmers who grow langsat in Sulewatang village and evaluate the feasibility of their agricultural activities using profit ratio (R/C) analysis. The primary data used were obtained from direct interviews with farmers who grow langsat, as well as secondary data collected from related institutions. The analysis method includes calculating total income (TR = P × Q), total costs (TC = FC + VC), and profit ratio (R/C = TR ÷ TC). The results showed that the average income of farmers who grow langsat reached 2,241,190 Indonesian rupiah, with a total production cost of 360,769 Indonesian rupiah. Thus, the farmer's net income was 1,880,421 Indonesian rupiah. The profitability coefficient (R/C) value of 6.21 indicates that R/C > 1, which means that langsat cultivation in Sulewatang village is profitable and feasible to be further developed.